2016
DOI: 10.1093/jscr/rjw185
|View full text |Cite
|
Sign up to set email alerts
|

Case report: successful open resection of a symptomatic giant liver haemangioma during the second trimester of pregnancy

Abstract: Liver haemangiomas are consistently reported to be the commonest benign liver tumours and are most often incidental findings in asymptomatic individuals. Large lesions can become symptomatic, spontaneously rupture or result in a consumptive coagulopathy known as Kasabach–Merrit Syndrome. It is believed that the female sex hormones, particularly oestrogen, have an influence on haemangioma development and growth. The optimal management of large haemangiomas during the hyperoestrogenic state of pregnancy is poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This is one of the first case reports describing a multidisciplinary management strategy for treating a ruptured hepatic adenoma during pregnancy including those of obstetrics and gynaecology, general surgery and IR. Other case reports exist discussing the resection of a hepatic mass during pregnancy, but this was prior and separate to delivery of the infant 7 8. Our patient and her infant had a good outcome despite the large blood loss, mainly due to early detection of maternal and fetal compromise and expeditious exploratory laparotomy and liver packing by the acute care general surgery team with definitive control by the IR team.…”
Section: Discussionmentioning
confidence: 69%
“…This is one of the first case reports describing a multidisciplinary management strategy for treating a ruptured hepatic adenoma during pregnancy including those of obstetrics and gynaecology, general surgery and IR. Other case reports exist discussing the resection of a hepatic mass during pregnancy, but this was prior and separate to delivery of the infant 7 8. Our patient and her infant had a good outcome despite the large blood loss, mainly due to early detection of maternal and fetal compromise and expeditious exploratory laparotomy and liver packing by the acute care general surgery team with definitive control by the IR team.…”
Section: Discussionmentioning
confidence: 69%
“…A study reported by Schnaper et al demonstrated that estrogen enhances endothelial cell proliferation, migration, and organization into capillary-like structures which leads to increased angiogenesis [ 8 ]. For this reason, accelerated growth caused by increased estrogen in pregnancy, as well as increased intra-abdominal pressure, and direct contact with a gravid uterus are possible mechanisms for increased risk of rupture during pregnancy [ 5 , 9 ].…”
Section: Discussionmentioning
confidence: 99%